IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILTY THE BODY SHOP INDONESIA SEBAGAI STRATEGI PASAR - DIAN IRMA APRIANTI; NOVEL REONALD (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2019)
Social responsibility must be carried out by the organization to all relevant parties both stakeholders and shareholders, the social obligation is aimed at consumers, employees, government and stakeholders. The study wanted to find out the extent of the role of Corporate Social Responsibility in this case abbreviated with CSR by The Body Shop Tbk in implementing the Cause Related Marketing theory program that was built through marketing antecedents and CSR by utilizing business capital and community welfare both economically, socially and culturally continuously .               The paper is based on building a foundation for analyzing the impact of The Body Shop Indonesia's Corporate Social Responsibility on various marketing actions namely Cause Related Marketing through various propositions based on the antecedents and consequences of business and social actions in society. The impact of this activity is correlated with three marketing performance parameters namely, economic, social measures. The results of this study indicate that The Body Shop Indonesia's Corporate Social Responsibility is in accordance with the rules of Corporate Social Responsibility of Companies in Indonesia